Methods and clinical outcomes of in situ fenestration for aortic arch revascularization during thoracic endovascular aortic repair. (August 2020) - Li, HL; Chan, YC; Jia, HY; Cheng, SW
Objective: Despite endovascular advances in fenestrated and branched devices, thoracic endovascular aortic repair (TEVAR) for arch pathologies remains challenging. The aim of this study was to provide a contemporary review on the current evidence for in situ fenestration during TEVAR and to evaluate its short- and mid-term clinical outcome in the management of arch pathology. Methods: A systematic literature review on in situ fenestration of thoracic aortic stent-graft from January 2003 to September 2018 was performed under the instruction of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. Results: Our initial search yielded 169 studies, of which 21 articles were relevant to the topic and were finally included. One hundred and forty-five in situ fenestration procedures in 99 patients were reviewed, involving 25 innominate arteries (17%), 33 left common carotid arteries (23%) and 87 left subclavian arteries (60%). Twelve patients (12/99, 12%) had two-vessel fenestration and three-vessel fenestration was performed in 17 patients (17/99, 17%). Technical success was achieved in 136 arteries (136/145, 93%). Talent/Valiant with monofilament twill woven polyester fabric was the most common (50/99, 51%) stent-graft used for fenestration. Three methods reported for in situ fenestration were needle, laser and radiofrequency. Needle was the most frequently used device for fenestration, which was performed in 60 patients (60/99, 61%). Three patients (3/99, 3%) died with 30 days, none were in situ fenestration TEVAR procedure-related. Perioperative complications including one (1%) retrograde type A aortic dissection, two (2%) type II endoleaks, and three (3%) strokes were reported. The pooled estimate for overall technical success, perioperative mortality and stroke was 88.3% (95% CI, 78.6%–93.9%), 5.9% (95% CI, 2.5%–13.4%) and 9.5% (95% CI, 4.1%–20.6%), respectively. Four patients (4/96, 4%) died during follow-up, none were aortic-related. All the fenestration bridging stents were reportedly patent, with only 1 (1/96, 1%) asymptomatic left subclavian stent stenosis. Two patients (2/96, 2%) with type II endoleak from left subclavian artery required secondary intervention. Conclusion: In situ fenestration appeared to be a feasible and effective method to extend proximal landing zone during TEVAR. It had an acceptable short-term result with high technical success and low fenestration related morbidity. Long-term durability data were lacking, and there was no high level evidence to recommend the routine use of in situ fenestration TEVAR for the management of arch pathology.